The Influence of Social Media Marketing on Brand Equity and Consumer Behavior of ABS Mineral Water in Kendari - Muhammad Aditya Maryadi; Muh. Nur; Nofal Supriaddin (Jurnal Indonesia Sosial Teknologi, 2025)
This study aims to analyze the effect of social media marketing on brand equity and consumer behavior of ABS mineral water in Kendari. The research uses a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The sample consists of 164 respondents who are ABS mineral water consumers and active social media users in Kendari City. Data collection was conducted through questionnaires using a Likert scale. The results show that social media marketing has a positive and significant effect on consumer behavior (path coefficient 0.626, p-value 0.00 < 0.05) and brand equity (path coefficient 0.721, p-value 0.00 < 0.05). Brand equity has a positive but limited significant effect on consumer behavior (path coefficient 0.152, p-value 0.050). However, brand equity does not significantly mediate the relationship between social media marketing and consumer behavior (path coefficient 0.110, p-value 0.056 > 0.05). The study concludes that social media marketing is more effective in directly influencing consumer behavior rather than through brand equity mediation in the context of ABS mineral water in Kendari.